The Song of the Sea - Russell, Brian D. (Peter Lang Inc., 2007)
The Song of the Sea: The Date of Composition and Influence of Exodus 15:1-21 offers a thorough exegetical study of the Song and its intertextual influence across the Hebrew Bible. It argues through a convergence of three lines of evidence – linguistic, historical, and intertextual – for a composition of the poetic sections of Exodus 15:1-21 in the mid-twelfth century b.c.e. Courses on the book of Exodus, Hebrew poetry, or intertextuality in the Hebrew Bible will find this text useful. «Brian D. Russell offers a close, well-informed literary-critical reading of the Song of the Sea in Exodus 15 and an insightful investigation of the Song’s interpretive trajectory and theological significance in the development of ancient Israel’s scriptural traditions. His analysis brings into clear focus the centrality of the Song in the compositional history and literary structure of the book of Exodus. Beyond this, Russell carefully examines the influence of the Song’s distinctive language and themes on later compositions, especially Psalms 74, 77, and 78, whose headings ascribe them to the Asaphite guild of cultic singers. In response to the contrary position of Martin Brenner in particular, Russell argues that the intertextual evidence favors a twelfth century date for the Song’s composition, providing renewed support for the view defended on linguistic grounds by Frank M. Cross and David Noel Freedman a generation ago. Thus, this book makes a contribution both as exegesis of a keynote biblical text and as engagement in an ongoing scholarly conversation about the early history of Israelite literature.» (S. Dean McBride Jr., Cyrus H. McCormick Professor of Hebrew and Old Testament Interpretation, Union Theological Seminary and Presbyterian School of Christian Education) «‘The Song of the Sea: The Date of Composition and Influence of Exodus 15:1-21’ presents a fresh analysis of an old crux in biblical interpretation. The Song of the Sea has long been a vexing text for everyone interested in Pentateuchal studies in general and in the book of Exodus in particular, as well as for researchers of the date and nature of early Hebrew poetry. A strength of Brian D. Russell’s work is his willingness to employ a gamut of methodological approaches, both diachronic and synchronic, including philology and comparative analysis as well as innerbiblical exegesis and rhetorical criticism. His conclusions about the date of the Song of the Sea are well-argued and convincing, and especially helpful is Russell’s comparison of the Song with the Psalms of Asaph as a means of establishing a ‘terminus ad quem’ for Exodus 15:1-21. This book will be foundational for all studies of the Song of the Sea for many years to come.» (Bill T. Arnold, Professor of Old Testament & Semitic Languages, Vice President of Academic Affairs/Provost, Asbury Theological Seminary)...
10.3726/978-1-4539-0684-2
Keywords: Exegese; Datierung; Textgeschichte